Enhancement of safety and comfort of cyclists at intersections. Issue 6 (6th March 2018) - Lu, Meng; Blokpoel, Robbin; Joueiai, Mahtab
Abstract : Cyclist safety is increasingly becoming a societal problem in Europe, as shown by road safety statistics. Frequent stops for red traffic lights at intersections are experienced by cyclists as a major inconvenience. This study introduces a green wave concept for cyclists, with focus on the traffic management and control aspects under cooperative intelligent transport systems applications. It especially addresses increasing stability of the adaptive control system, to overcome the drawbacks of both actuated and traditional adaptive control (which are too unpredictable for a green wave speed advice). In addition, solutions for avoiding increased delays for other traffic are investigated, as generally result from a classic green wave approach (with only fixed‐time control) and traditional adaptive control. This study introduces an adaptive control algorithm for a real‐time model‐predictive controller and implements a plan‐deviation cost function to address stabilisation. Simulation results show that the developed method increases stability of the adaptive control system, limits extra delays for other traffic and yields a high success rate for the green wave concept.